Rituximab as therapy to induce remission after relapse in ANCA-associated vasculitis. Issue 9 (24th June 2020) - Smith, Rona M; Jones, Rachel Bronwen; Specks, Ulrich; Bond, Simon; Nodale, Marianna; Aljayyousi, Reem; Andrews, Jacqueline; Bruchfeld, Annette; Camilleri, Brian; Carette, Simon; Cheung, Chee Kay; Derebail, Vimal; et al.
Abstract : Objectives: Evaluation of rituximab and glucocorticoids as therapy to induce remission after relapse in ANCA-associated vasculitis (AAV) in a prospective observational cohort of patients enrolled into the induction phase of the RITAZAREM trial. Methods: Patients relapsing with granulomatosis with polyangiitis or microscopic polyangiitis were prospectively enrolled and received remission-induction therapy with rituximab (4×375 mg/m 2 ) and a higher or lower dose glucocorticoid regimen, depending on physician choice: reducing from either 1 mg/kg/day or 0.5 mg/kg/day to 10 mg/day by 4 months. Patients in this cohort achieving remission were subsequently randomised to receive one of two regimens to prevent relapse. Results: 188 patients were studied: 95/188 (51%) men, median age 59 years (range 19–89), prior disease duration 5.0 years (range 0.4–34.5). 149/188 (79%) had previously received cyclophosphamide and 67/188 (36%) rituximab. 119/188 (63%) of relapses had at least one major disease activity item, and 54/188 (29%) received the higher dose glucocorticoid regimen. 171/188 (90%) patients achieved remission by 4 months. Only six patients (3.2% of the study population) did not achieve disease control at month 4. Four patients died in the induction phase due to pneumonia (2), cerebrovascular accident (1), and active vasculitis (1). 41 severe adverse events occurred in 27 patients, including 13 severe infections. Conclusions: This large prospective cohort of patients with relapsing AAV treated with rituximab in conjunction with glucocorticoids demonstrated a high level of efficacy for the reinduction of remission in patients with AAV who have relapsed, with a similar safety profile to previous studies.